2022
DOI: 10.1186/s42269-022-00810-3
|View full text |Cite
|
Sign up to set email alerts
|

Breast-feeding practices and maternal employment in health facilities of Lira District, Northern Uganda

Abstract: Background In Uganda, many working mothers stop breast-feeding before the end of the mandatory maternity leave of 60 days. Inadequate breast-feeding is a risk factor for infant morbidity and mortality. Thus, understanding of the factors that influence breast-feeding is essential so as to advocate for the appropriate breast-feeding practices. This cross-sectional study assessed the pre-lacteal feeding (PLF), early initiation of breast-feeding (EIBF) and exclusive breast-feeding (EBF) and the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Children in this age category were additionally fed on mashed and or other liquid foods, coming from other food groups such as other liquids other than milk, grains, roots and tubers and minimally other dairy products. These results reflect similarly to the other recent studies on exclusive breast feeding that found 43.9% and 42.8% prevalence of exclusive breast feeding among different categories of mothers of children under 6 months of age in northern and central Uganda respectively[ 26 , 27 ]. On the other hand, although complementary feeding is safe to introduce after six months, this study reveals that the types of foods fed to children above 6 months in this case was predominantly from high starch sources such as grains, roots and tuber-based foods.…”
Section: Discussionsupporting
confidence: 91%
“…Children in this age category were additionally fed on mashed and or other liquid foods, coming from other food groups such as other liquids other than milk, grains, roots and tubers and minimally other dairy products. These results reflect similarly to the other recent studies on exclusive breast feeding that found 43.9% and 42.8% prevalence of exclusive breast feeding among different categories of mothers of children under 6 months of age in northern and central Uganda respectively[ 26 , 27 ]. On the other hand, although complementary feeding is safe to introduce after six months, this study reveals that the types of foods fed to children above 6 months in this case was predominantly from high starch sources such as grains, roots and tuber-based foods.…”
Section: Discussionsupporting
confidence: 91%
“…<3 or 4 mo) were associated with a lower probability of EBF than longer leaves [ 12 , 16 , 42 ]. Similarly, not receiving any paid leave was negatively associated with EBF [ 58 ].…”
Section: Resultsmentioning
confidence: 99%